Enabling Export Diversification - World Bank (World Bank, Washington, DC, 2018)
Bangladesh’s export growth has been remarkable. Bangladesh aims to generate $54.1 billion in export earnings by FY2020, a significant increase over the $35 billion earned in FY2015-16. The leading sector, textiles and apparels, usually referred to as ready-made garments (RMG), has created 4 million jobs overall and accounts for 82 percent of Bangladesh’s exports. RMG exports have shown signs of deceleration in the recent past but the momentum has picked up in FY2018. At the same time, several other less dominant but promising sectors are showing a positive export growth trend and could possibly drive export diversification and job creation in the future.However, the composition of the export basket has not changed much over the past two decades.Bangladesh’s HHI (Herfindahl-Hirschmann Index), that measures the level of sectoral concentration in exports is about five times that of other export-driven economies such as Thailand, China and Vietnam. During the last two decades, Vietnam expanded its export basket from agriculture to include machinery, footwear and electronics through national-level strategies and policy reforms to support specific sectors. However, Bangladesh continues to be primarily an RMG exporter.